Microparticles from apoptotic monocytes induce transient platelet recruitment and tissue factor expression by cultured human vascular endothelial cells via a redox-sensitive mechanism - Essayagh, Sanah; Xuereb, Jean-Marie; Terrisse, Anne-Dominique; Tellier-Cirioni, Lise; Pipy, Bernard; Sié, Pierre (Thrombosis and Haemostasis, 2007)
Circulating microparticles derived from different types of blood cells have been reported to impair endothelial function and to induce pro-inflammatory and prothrombotic endothelial phenotypes. Although the number of monocyte-derived microparticles (M-MPs) is elevated in the blood of patients with various inflammatory conditions, their interaction with endothelial cells has been poorly investigated so far. In this study, we produced microparticles in vitro from apoptotic human monocytes and examined the effects of their interaction with cultured human umbilical vascular endothelial cells (HUVECs). We found that low concentrations of M-MPs induced the production of reactive oxygen species (ROS), mainly anion superoxide, by the endothelial cells. At sub-toxic concentrations, M-MPs induced a rapid expression of von Willebrand factor at the cell surface, which mediated the transient attachment of non-activated platelets to the endothelium in flow conditions. In parallel, M-MPs up-regulated the expression of functional tissue factor by the endothelial cells. ROS controlled these two major changes and the process involved the phosphorylation of p38 mitogen activated protein kinase. We conclude that M-MPs may contribute to thrombotic events by producing redox signalling in endothelial cells.
Keywords: Endothelial cells; microparticles; monocytes; oxidative stress